KARAKTERISTIK BRIKET ARANG DARI LIMBAH SERBUK PENGGERGAJIAN KAYU KARET DAN LIMBAH SERBUK PENGGERGAJIAN KAYU MERANTI MERAH - Dian Taufani; Yuniarti Yuniarti; Budi Sutiya (Universitas Lambung Mangkurat, 2023)
Charcoal briquettes made from a mixture of rubber wood sawing powder and red meranti sawdust is one of the efforts to utilize waste. The purpose of this study was to determine the characteristics of charcoal briquettes from a mixture of rubber sawdust waste and red meranti sawdust waste. The mixture of raw materials used 5 treatments, namely 1) 100% rubber wood charcoal briquettes; 2) 75% rubber wood charcoal briquettes and 25% red meranti wood charcoal; 3) 50% rubber wood charcoal briquettes and 50% red meranti wood charcoal; 4) 25% rubber wood charcoal briquettes and 75% red meranti wood charcoal; and 5) 100% red meranti wood charcoal briquettes. The resulting data were then analyzed by means of variance and compared with SNI. The quality of charcoal briquettes was not affected by the composition of the mixture of rubber wood charcoal briquettes and red meranti wood charcoal briquettes. Treatment with 100% rubber wood charcoal briquettes as raw material, without a mixture of red meranti wood charcoal briquettes, was charcoal briquettes with the quality closest to SNI standards, in the form of volatile substances, and calorific value. Other parameters such as moisture content, density, ash content and bound carbon still do not meet the SNI standardBriket arang yang terbuat dari campuran serbuk penggergajian kayu karet dan serbuk penggergajian kayu meranti merah merupakan salah satu upaya pemanfaatan limbah. Tujuan penelitian ini adalah mengetahui karakteristik briket arang dari campuran limbah serbuk penggergajian kayu karet dan limbah serbuk penggergajian kayu meranti merah. Campuran bahan baku menggunakan 5 perlakuan yaitu 1) briket arang kayu karet 100%; 2) briket arang kayu karet 75% dan arang kayu meranti merah 25%; 3) briket arang kayu karet 50% dan arang kayu meranti merah 50%, 4) briket arang kayu karet 25% dan arang kayu meranti merah 75%; dan 5) briket arang kayu meranti merah 100%. Data yang dihasilkan selanjutnya dianalisis dengan sidik ragam dan dibandingkan dengan SNI. Kualitas briket arang tidak dipengaruhi oleh komposisi campuran briket arang kayu karet dan briket arang kayu meranti merah. Perlakuan dengan bahan baku briket arang kayu karet 100%, tanpa campuran briket arang kayu meranti merah, merupakan briket arang dengan kualitas yang paling mendekati standar SNI, berupa zat terbang, dan nilai kalor. Parameter lainnya berupa kadar air, kerapatan, kadar abu dan karbon terikat masih belum memenuhi standar SNI.